THE ACTUALIZATION OF RELIGIOUS AND CULTURAL VALUES AS A CONTROLLING FACTOR FOR THE SOCIAL EFFECTS OF TERRORISM: Case Terrorized Murder in Lembantongoa Village Palolo sub-district, Sigi district. - Jamaluddin; Abdul Hakim; Nisbah (LPPM Universitas Tadulako, 2023)
This study aims to determine the extent to which religious and cultural values in the Lembantongoa Village community strengthen their social group identity, as well as the source of ideas, thoughts, ways, which are useful as a barrier and inhibiting factor for the creation of destructive social turmoil effects due to the terrorist movement. The results of this study reveal facts that explain 1) the influence of religion and culture is still quite strong, manifested in community behavior in the form of adherence to customary norms; life cycle ceremonies, customary laws, social organizations, always strengthen their structural and cultural identity, 2) the real act of murder terror in Lembantongoa Village is an attempt to manipulate the power of religion and culture as a means of justifying social turmoil, 3) the perpetrators of terror are the continuity of terrorist actors